2012
DOI: 10.2147/opth.s22991
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral choroidal neovascularization associated with optic nerve head drusen treated by antivascular endothelial growth factor therapy

Abstract: ObjectiveTo report a good clinical outcome in a patient with bilateral choroidal neovascularization (CNV) associated with optic nerve head drusen (ONHD) treated with intravitreal ranibizumab injection.MethodsA 12-year-old girl was referred for loss of right eye vision detected in a routine check-up. Best-corrected visual acuity (BCVA) was hand movements in the right eye and 0.9 in the left eye. Funduscopy revealed the presence of superficial and buried bilateral ONHD, which was confirmed by ultrasonography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…No recurrence was observed during the follow-up period. Similar results have been reported in the literature 6 7. Gregory-Evans et al 6 used three monthly intravitreal ranibizumab injections to treat CNV secondary to ONHD in an 11-year-old boy.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…No recurrence was observed during the follow-up period. Similar results have been reported in the literature 6 7. Gregory-Evans et al 6 used three monthly intravitreal ranibizumab injections to treat CNV secondary to ONHD in an 11-year-old boy.…”
Section: Discussionsupporting
confidence: 79%
“…They reported that subretinal fluid was disappeared and BCVA improved to 20/60 from hand movements. After 12 months’ of follow-up BCVA was 20/60 7. Knape et al 8 reported their successful treatment for CNV secondary to ONHD in a 5-year-old boy.…”
Section: Discussionmentioning
confidence: 97%
“…Successful treatment of optic disc drusen with CNVM has been reported with surgery, 123; 200 laser photocoagulation, 38 photodynamic therapy, 29; 193 and more recently intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents. 2; 9; 37; 69; 84; 99; 175 Both bevacizumab and ranibizumab have been used successfully in children with CNVM secondary to optic disc drusen as young as five years of age. 9; 99 Although some clinicians use anti-VEGF agents to treat infants with retinopathy of prematurity, concerns still exist regarding the safety of these drugs, particularly bevacizumab, in the pediatric population.…”
Section: Treatmentmentioning
confidence: 99%
“…Possible mechanisms involved in this complication include the compressive effect of drusen on the surrounding blood vessels, which leads to mechanical impairment of peripapillary vascular integrity, vascular congestion, or ischemia. Retinal ischemia and the release of VEGF may be the factors that trigger the development of CNV [8,9]. Treatment must be provided if vision is jeopardized.…”
Section: Discussionmentioning
confidence: 99%